Performance compariaon bertween prefabicated vertical drains(PVD)and electricak vertical drains (EVS)on marine soil - Mohammad Nabil Fikri Bin Razali, Mohammad Nabil Fikri (2009)
This report basically discusses the interim research done and basic understanding of the chosen topic, which is Performance Comparison between Prefabricated Vertical Drains (PVD) and Electrical Vertical Drains (EVD) on Marine Soil.